2019
DOI: 10.1001/jama.2019.4783
|View full text |Cite
|
Sign up to set email alerts
|

Association of Unrecognized Obstructive Sleep Apnea With Postoperative Cardiovascular Events in Patients Undergoing Major Noncardiac Surgery

Abstract: ; for the Postoperative Vascular Complications in Unrecognized Obstructive Sleep Apnea (POSA) Study Investigators IMPORTANCE Unrecognized obstructive sleep apnea increases cardiovascular risks in the general population, but whether obstructive sleep apnea poses a similar risk in the perioperative period remains uncertain. OBJECTIVES To determine the association between obstructive sleep apnea and 30-day risk of cardiovascular complications after major noncardiac surgery. DESIGN, SETTING, AND PARTICIPANTS Prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
208
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 228 publications
(224 citation statements)
references
References 38 publications
8
208
2
6
Order By: Relevance
“…No previous study on the association between DM and CABG outcomes has reported the additional prognostic effect of sleep apnea [3][4][5][6][7][8]. Recently, two relatively large-scale studies demonstrated an independent association of sleep apnea with adverse cardiovascular events in patients undergoing CABG and major non-cardiac surgery [16,25]. The predictive effects of sleep apnea and DM for adverse cardiovascular events were reported to be additive in patients undergoing percutaneous coronary intervention [26].…”
Section: Discussionmentioning
confidence: 99%
“…No previous study on the association between DM and CABG outcomes has reported the additional prognostic effect of sleep apnea [3][4][5][6][7][8]. Recently, two relatively large-scale studies demonstrated an independent association of sleep apnea with adverse cardiovascular events in patients undergoing CABG and major non-cardiac surgery [16,25]. The predictive effects of sleep apnea and DM for adverse cardiovascular events were reported to be additive in patients undergoing percutaneous coronary intervention [26].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly half of the episodes detected by capnography were Levels I and II apnea notifications (Table 3). At trial outset, the apnea notification delay was decreased from device default of 30 to 10 s, to align with detection of OSA, which is a challenge in the postoperative setting and is associated with increased cardiovascular complications when severe OSA goes unrecognized [25,26]. If this notification delay was changed to the default setting (30 s), it would likely report fewer episodes and could reduce alarm fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…11 In a recent prospective cohort study of 1,218 patients undergoing elective non-cardiac surgery, severe undiagnosed OSA was associated with a two-fold increased risk of cardiovascular complications (adjusted hazard ratio, 2.23) and longer duration of hypoxemia. 5 As well, the mean cumulative duration of SpO 2 \ 80% during the first three postoperative nights for patients with cardiovascular complications was increased compared with patients with no cardiovascular complications (23.1 [95% confidence interval (CI), 15.5 to 27.7] min vs 10.2 [95% CI, 7.8 to 10.9] min). In another study, we showed an association between preoperative mean SpO 2 \93% and increased risk of postoperative complications.…”
mentioning
confidence: 89%
“…4 Furthermore, a large proportion of patients undergoing surgery have undiagnosed and untreated OSA and are at the highest risk of postoperative complications. 5 The real-world scenario is less than ideal; short of PAP therapy, the default alternative on the general care ward is supplemental oxygen.…”
mentioning
confidence: 99%
See 1 more Smart Citation